2020
DOI: 10.1101/2020.01.15.905802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of b-value on estimates of apparent fibre density

Abstract: Recent advances in diffusion magnetic resonance imaging (dMRI) analysis techniques have improved our understanding of fibre-specific variations in white matter microstructure.Increasingly, studies are adopting multi-shell dMRI acquisitions to improve the robustness of dMRI-based inferences. However, the impact of b-value choice on the estimation of dMRI measures such as apparent fibre density (AFD) derived from spherical deconvolution is not known. Here, we investigate the impact of b-value sampling scheme on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Thirdly, our diffusion weighted data were acquired with 32 diffusion directions and a single b-value of 1000 s/mm 2 which is not optimal for CSD or apparent fiber density modelling. Indeed, it has been shown that the best conditions to perform CSD were higher b values and higher angular resolution 64 and that both parameters influence apparent fiber density measure 65 . Thus, our measure of apparent fiber density might not be optimal and might influence our finding of wide overlap between FD and FA changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our diffusion weighted data were acquired with 32 diffusion directions and a single b-value of 1000 s/mm 2 which is not optimal for CSD or apparent fiber density modelling. Indeed, it has been shown that the best conditions to perform CSD were higher b values and higher angular resolution 64 and that both parameters influence apparent fiber density measure 65 . Thus, our measure of apparent fiber density might not be optimal and might influence our finding of wide overlap between FD and FA changes.…”
Section: Discussionmentioning
confidence: 99%
“…Note: See Raffelt et al (2017) for complete descriptions of these measures. *The interpretation of these measures as related to the microstructure of ‘axons’ depends on the strength of the diffusion weighting ( Genc et al, 2020 ). Alt-text: Box 1 …”
Section: Introductionmentioning
confidence: 99%
“…Compared to commonly used DTI metrics such as FA or mean diffusivity (MD), fixel-based FD is a stronger candidate for signifying microstructural organisation ( Kelley et al, 2019 ), as it is both sensitive (at high b-values) to the intra-axonal signal ( Genc et al, 2020 ), and specific to fibre populations ( Raffelt et al, 2015 ). By comparison, FA measurements can be conflated by crossing fibres and extra-axonal signal contamination ( Jones et al, 2013 ; Bach et al, 2014 ; Beaulieu, 2009 ), making biophysical interpretations challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In TBSS, false positives may be responsible for our ndings, having been shown to arise from method-inherent issues like considerable noise dependency and projection inaccuracies in regions of crossing bres 43 . Similarly, false-negative ndings by FBA have to be considered as a cause, potentially arising from the relatively low b-value (b = 1000mm/s²) leading to insu cient suppression of the extraaxonal compartment 52 .…”
Section: Discussionmentioning
confidence: 99%